Rapid Displacement of SARS-CoV-2 Variants within Japan Correlates with Cycle Threshold Values on Routine RT-PCR Testing - Wright, Danelle; Chan, Carmen; Chaochaisit, Wirawit; Ogawa, Mio; Tanaka, Junko; Nozaki, Satoshi; Narita, Shinji; Shimizu, Eisuke; Aoshima, Hideyuki; Baran, Iri Sato (Archives of Clinical and Biomedical Research, 2022)
Background: The rapid spread of SARS-CoV-2 worldwide has led to the emergence of new variants due to the presence of mutations that alter viral characteristics, but there have been few studies on trends in viral lineages in Japan, an island country. We hypothesized that changes in cycle threshold (Ct) values on reverse transcription polymerase chain reaction (RT-PCR) reflect the prevalent variants during a given period. Methods: We performed next-generation sequencing of positive samples to identify the viral lineages in Japan in 2021 and compared variant prevalence with the average Ct values on routine RT-PCR using 4 primer sets. Results: Based on 3 sequencing runs, the highly transmissible Alpha variant, which prevailed over other lineages, such as R.1, from April 2021, was dominated by the even stronger Delta variant between July and August 2021 in Japan. The decrease in our routine RT-PCR Ct values with 4 primer sets correlated with these fluctuations in lineage prevalence over time. Conclusions: We confirmed that our RT-PCR protocol reflects the trends in SARS-CoV-2 variant prevalence over time regardless of sequence mutation. This may aid in the tracking of new variants in the population.